2007
DOI: 10.1002/jbm.a.31356
|View full text |Cite
|
Sign up to set email alerts
|

Osteoblast differentiation in vitro and in vivo promoted by Osterix

Abstract: C3H10T1/2/Osx, a stably transfected cell line with Osterix (Osx), was produced and chondrocytic and osteoblastic differentiation were studied in vitro. Osx promoted osteoblastic lineage that was dexamethasone dependent. Furthermore, in vivo, Osx induced ectopic mineralization in a heterotopic mouse muscle model. Skeletogenesis involves a cascade of molecular activities sequentially performed by osteoblasts and chondroblasts. A transcriptional factor gene Osx appears to influence cell disposition toward the cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
51
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 25 publications
3
51
0
Order By: Relevance
“…Osx, downstream of Runx2, is an osteoblast-specific transcription factor essential for osteoblast differentiation and bone formation (26). Forced expression of Osx in vitro induces the expression of several osteoblastic genes, including Col1α1 and osteocalcin (27,28). The present study demonstrated that quercetin restored the expression of Osx and Runx2, which were suppressed by LPS in MC3T3-E1 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Osx, downstream of Runx2, is an osteoblast-specific transcription factor essential for osteoblast differentiation and bone formation (26). Forced expression of Osx in vitro induces the expression of several osteoblastic genes, including Col1α1 and osteocalcin (27,28). The present study demonstrated that quercetin restored the expression of Osx and Runx2, which were suppressed by LPS in MC3T3-E1 cells.…”
Section: Discussionsupporting
confidence: 57%
“…Runx2 (Cbfa1) and ALP have been suggested to be involved in the early-stage molecular events of osteoblast differentiation [31, 32], whereas OSX and OCN are involved in the late-stage molecular events [23, 33, 34]. In this study, pretreatment with quercetin significantly restored the LPS-suppressed mRNA and protein expression of ALP, Runx2, OSX and OCN in MC3T3-E1 cells in a dose-dependent manner.…”
Section: Discussionmentioning
confidence: 56%
“…5). Interestingly, the most sensitively upregulated gene expression in response to BMP-7 stimulation was the transcription factor SP7, which was recently reported to promote osteogenic differentiation in vitro and in vivo using the gene overexpression approach in mouse models [Fu et al, 2007]. In contrast to its upstream gene RUNX2, SP7 expression was largely and stably enhanced by BMP-7 supplementation up to 14 days, which suggests a potential mechanism of BMP-7 function in the osteogenic differentiation of BM MSCs.…”
Section: Discussionmentioning
confidence: 97%